Refusal and linguistic politeness: a comparative study of Malay speakers and native speakers of english - Norma, Saad (2016)
Speech act of refusal requires a high level of pragmatic competence because it tends to risk interpersonal relationship between speakers. Similar studies on MSE and NSE refusal strategies have been conducted utilising a Discourse Completion Test however, the findings have not reflected real life situations. Hence, a study which compares the Malay Speakers of English (MSE) and the Native Speakers of English (NSE) will provide insights into the realisation of the speech act of refusal. This study employed an Enhanced Open Role-play to examine the types, content and distributional order of refusal and politeness strategies. Data were obtained from 12 MSE and 12 NSE participants who had refused to the higher and equal status interlocutors’ offers, invitations and requests. Qualitative data analytic methods were used to analyse the data which were classified into semantic refusal strategies and politeness strategies. Brown’s and Levinson’s politeness theory, Hofstede’s cultural dimensions and Hall’s high- and low-context cultures were utilized to explain the findings of the study. The findings revealed that the two groups employed similar strategies which reflect a firm yet conciliatory approach when refusing to the higher status interlocutor’s offers and requests but were rather antagonistic toward their equal’s offers and requests. Nevertheless, both groups employed amiable strategies when refusing to the higher and equal status interlocutors’ invitations. The strategies reflect their adaptation to the different status of interlocutors and the situations. However, the MSE and NSE differ in terms of the degree of directness and cultural values. The NSE showed a higher use of direct strategies and the content of their indirect strategies and adjuncts to refusal strategies reflect the western individualistic values whereas the MSEs’ exhibit the eastern values which prioritize group’s importance. These findings provide further insights on the complexities of refusal interaction. These refusal interaction patterns could be used by English language teachers as pragmatic input to develop English as a Second Language students’ ability to use socially appropriate language for the situation they encounter.